Rehabilitation of Surgically Resected Soft Palate with Interim Velopharyngeal Obturator - Bilal Ahmed (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
Rehabilitation of surgical resection defects is always a challenging clinical scenario. These defects pose a major physiological and psychological threat not only to the patients, but to the entire family. A multidisciplinary team approach, thorough investigation, long term follow up, proper counselling and sympathetic attitude may help to bring these suffering patients back to normal life stream. Recent advancements in Dental Materials, CAD CAM, Laser Technology and Ossseo integrated Implants have revolutionized the treatment outcomes. However in certain clinical case scenarios, conventional prosthodontic principles and routinely available materials are still the gold standards. This case report presents the prosthodontic rehabilitation of soft palate after surgical resection due to adenoid cystic cell carcinoma.